Relative contraindications to percutaneous endoscopic gastrostomy (review of literature) - Yu. O. Zharikov; M. Kh. Gurtsiev; S. Zh. Antonyan; S. F. Askerova; E. I. Chairkina; P. A. Yartsev (Вестник хирургии имени И.И. Грекова)
Percutaneous endoscopic gastrostomy is the most common method for enteral nutrition in intensive care patients with dysphagia syndrome. The advantages of the method are the minimally invasive nature and duration of the operation, which also determines a small percentage of postoperative complications. There are many literary sources devoted to the most common complications, indications and contraindications to the procedure. The objective of the literature review was to analyze the data on the relative contraindications to percutaneous endoscopic gastrostomy and the tactics used by specialists to minimize the risks of performing surgery in this group of patients. Correction of the general condition and concomitant somatic diseases in the patient as well as a thorough risk assessment have the greatest impact on the immediate results of the operation.